Answer:
Option A is correct.
Explanation:
Common Ratio of Geometric series is obtained by dividing by each next term of the series to its previous term
here in the problem two consecutive terms are -1 and -i
so dividing -i by -1 in order to find common ratio
r =
![(-i)/(-1) = i](https://img.qammunity.org/2020/formulas/mathematics/high-school/7hlvfpyvqtbwrwkpaot1twcpv6xc2gzbm0.png)
Since here common ratio is i
next 3 terms are given by
![T_4= rT_3\\T_4= (i)((-i) = -i^2=-(-1) = 1\\T_5 =rT_4= (i) (1)= i \\T_6= rT_5 = (i)(i) = i^2= -1 \\](https://img.qammunity.org/2020/formulas/mathematics/high-school/mcoh5aeqc5l4n6csna7wf8kkoq0rwkwj2c.png)
Therefore common ratio is i and next three terms are 1,i and -1
Therefore option A is correct .